Gay Men's Digital Cultures Beyond Gaydar And Grindr: Line Use In The Gay Chinese Diaspora Of Australia - Cassidy, Elija; Wang, Wilfred (AoIR Selected Papers of Internet Research, 2017)
Research about gay men’s digital cultures tends to focus predominantly on Western, English-language based dating applications and users; meaning little attention has yet been paid to minority and non-Western gay male groups and services. Drawing on data collected from an initial phase of participant observation on LINE, a popular instant text and voice messenger application in Asia, this paper examines social media use and the formation of gay Chinese diasporic identity in Australia. Findings indicate that LINE groups for this community are an important site for users to negotiate new cultural selves, to develop strategic personal and cultural networks in a new environment, and to remediate their engagements with other, more mainstream services such as Grindr, Facebook and WeChat.